Есть ли в Турции ящурка разноцветная — Eremias arguta (Pall.)? - Щербак, Н.Н. (Вестник зоологии, 1969)
On the basis of the critical analysis of the literature (Bodenheimer, 1944, Mertens. 1952) the inhabitance of Eremias arguta transcaucasica D a r. species, new for Turkey fauna, was established in the region of Lake Van.